Shielding Properties Of Fly Ash Based Geopolymer Using Barium Sulphate For Diagnostic Radiology - Shalbi, Sabri Mansur Himeedh (2018)
This work was conducted to study the properties of fly ash geopolymer (FAGP) in order to use as an alternative cement mortar (OPC) material as shielding material by adding barium sulphate (BaSO4) as an additional material. The fabrication of the FAGP involved the dissolution of aluminosilicate material in a highly alkaline solution and subsequent combination with sand. The shielding properties of FAGP were enhanced with the addition of BaSO4. The FAGP was dried in an oven for one day at 60 - 70 ℃, and then cooled at room temperature for 28 days.